User Engangement Pada Perpustakaan dan Pustakawan di Era Ekonomi Digital: Sebuah Narrative Literature Review - Rahayu, Rochani Nani (Jurnal IPI (Ikatan Pustakawan Indonesia), 2023)
Research to find out the methods used to involve users in libraries and librarians, was conducted using the narrative literature review method. Starting with a literature search, the Scopus database was selected, which is the largest database for abstracts, citations, and peer-reviewed scientific literature. A search strategy was carried out using the keywords: "user engagement" and (library or librarian), and the limitations for 2012-2022, with title, abstract and keyword fields. Found as many as 35 article titles. Furthermore, the articles were read carefully and researched, to select articles relevant to the research objectives, and obtained as many as 12 article titles. Based on the results and discussion of the 12 articles, it is known as many as 5 ways to involve users in library services as follows. The use of social media is in the first position with a total of 8 studies, the next is the use of Gamification, user campaigns and surveys, building collaboration and personal relationships, and the use of the LibraryThing application, each with 1 research title.